2022
DOI: 10.1021/acs.energyfuels.2c00443
|View full text |Cite
|
Sign up to set email alerts
|

Tuning CO2 Binding in Metal–Organic Framework Materials by Varying Metal Identity and Oxidation State

Abstract: CO2 adsorption from distributed and point sources has attracted significant interest in the recent past, and advanced sorbent design remains a fruitful avenue of research, yet structure–property relationships that capture the effect of an adsorption site coordination environment on binding characteristics remain (for the most part) elusive. Metal–organic framework (MOF) materials carry adsorption sites in highly well-defined coordination environments and present an opportunity for relating specific features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
(181 reference statements)
0
3
0
Order By: Relevance
“…44 On the one hand, the choice of metal needs to consider valence and coordination ability. 45 On the other hand, acidic-stable MOFs can be obtained by choosing to introduce high-priced metals (hard acids, such as Zr 4+ and Al 3+ ). Low-cost metals (soft acids, such as Co 2+ and Ni 2+ ) were combined to synthesize alkaline-resistant MOFs.…”
Section: Metal Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 On the one hand, the choice of metal needs to consider valence and coordination ability. 45 On the other hand, acidic-stable MOFs can be obtained by choosing to introduce high-priced metals (hard acids, such as Zr 4+ and Al 3+ ). Low-cost metals (soft acids, such as Co 2+ and Ni 2+ ) were combined to synthesize alkaline-resistant MOFs.…”
Section: Metal Componentsmentioning
confidence: 99%
“…The 3D orbital electronic structure of active sites of the bimetallic MOF was modulated, thus favoring the adsorption of the intermediate . On the one hand, the choice of metal needs to consider valence and coordination ability . On the other hand, acidic-stable MOFs can be obtained by choosing to introduce high-priced metals (hard acids, such as Zr 4+ and Al 3+ ).…”
Section: Catalyst Design Considerations For Co2rrmentioning
confidence: 99%
“…[256,257] Many articles confirmed that metal cations can be simply introduced into adsorbents via chemical reduction and cation exchange. [258,259] Such metal sites enable the easy approach of CO 2 molecules toward the pore surfaces and improve the gas-adsorbent interactions. Due to the high polarity and quadrupole moment of CO 2 , the selectivity is also enhanced over high-affinity binding sites.…”
Section: Open/unsaturated Metal Sitesmentioning
confidence: 99%